Basolateral Amygdala Serotonin 2C Receptor Regulates Emotional Disorder-Related Symptoms Induced by Chronic Methamphetamine Administration - Wang, Zhuo; Li, Chen; Ding, Jiuyang; Li, Yanning; Zhou, Zhihua; Huang, Yanjun; Wang, Xiaohan; Fan, Haoliang; Huang, Jian; He, Yitong; Li, Jianwei; Chen, Jun; et al. (Frontiers in Pharmacology, 2021)
Globally, methamphetamine (meth) is the second most abused drug, with psychotic symptoms being one of the most common adverse effects associated with its abuse. Emotional disorders induced by meth abuse have been widely reported both in human and animal models; however, the mechanisms underlying such disorders have not yet been fully elucidated. In this study, a chronic meth administration paradigm in mice was utilized to reveal the role of the brain serotoninergic pathway in depressive behaviors. After 4 weeks of meth administration, the animals exhibited significantly increased depressive symptoms. Molecular and morphological evidence showed that chronic meth administration reduced the expression of 5-HT rate-limiting enzyme-TPH2 in the dorsal raphe (DR) while also decreasing the concentrations of 5-HT and its metabolite 5-HIAA in the basolateral amygdala (BLA) nuclei. Alterations in both 5-HT and the 5-HT receptor levels occurred simultaneously; qPCR, western blot, and fluorescence analysis revealed that the expression of the 5-HT2C receptor (5-HT2CR) increased. Neuropharmacology and virus-mediated silencing strategies confirmed that targeting 5-HT2CR could reverse the depressive behaviors induced by chronic meth use. 5-HT2CR co-located with GABAergic interneurons in the BLA. Inactivation of 5-HT2CR in the BLA—the principal depression-related region of the brain—ameliorated the impaired GABAergic inhibition while decreasing BLA activation. Thus, herein, for the first time, we report that the abnormal regulation of 5-HT2CR is involved in the manifestation of depression-like symptoms induced by chronic meth use. Our study suggests that 5-HT2CR in the BLA is a promising clinical target for the treatment of meth-induced emotional disorders.